2012
DOI: 10.1094/pdis-07-12-0635-pdn
|View full text |Cite
|
Sign up to set email alerts
|

Storage Rot of Dragon Fruit Caused by Gilbertella persicaria

Abstract: In October 2011, a new disease of dragon fruit (Hylocereus costaricensis) was discovered in a fruit market in Yuanjiang, Yunnan Province, China. Small, light brown, water-soaked spots appeared initially and then coalesced, extending to the entire fruit in 6 days. Hyaline hyphae and light brown sporangia were observed over the entire surface of the infected fruit. On potato sucrose agar (PSA) the fungus produced a white, appressed colony that covered a 9-cm diameter petri dish in less than 5 days at 25°C. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 0 publications
2
15
0
2
Order By: Relevance
“…The morphology of G. persicaria structures is similar to that reported by diverse authors (Benny, 1991;Guo et al, 2012;Pinho et al, 2014). It is considered a monotypic species in its genus, which is located in the subfamily Gilbertelloideae and the family Choanephoraceae (Hyde et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The morphology of G. persicaria structures is similar to that reported by diverse authors (Benny, 1991;Guo et al, 2012;Pinho et al, 2014). It is considered a monotypic species in its genus, which is located in the subfamily Gilbertelloideae and the family Choanephoraceae (Hyde et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…Morphotype 1 (petaloid colonies, brown sporangia) was observed in 31% of the isolates, while the rest of the isolates presented morphotype 2 (69%). G. persicaria is a common pathogen in tropical and subtropical regions, causing the soft rot of tomato, pear, peach, pitahaya, jambolan (Ginting et al, 1996;Guo et al, 2012;Pinho et al, 2014) and recently, it was reported to have infected papaya fruits in the state of Colima, Mexico (Cruz-Lachica et al, 2016). This study reports the presence of this species in the states of Oaxaca and Veracruz, showing that it is present in other papaya producing regions and its distribution should be considered important.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Recently, G. persicaria has been reported to cause soft rot on dragon fruits (Hylocereus spp.) in China and Taiwan (Guo et al 2012;Lin et al 2014). To our knowledge, this is the first report of G. persicaria soft rot in eggplant fruit in mainland China.…”
mentioning
confidence: 99%